The huntress : a novel - Quinn, Kate (William Morrow, an imprint of HarperCollinsPublishers, 2019)
Stranded behind enemy lines, brave bomber pilot Nina Markova becomes the prey of a lethal Nazi murderess known as the Huntress and joins forces with a Nazi hunter and British war correspondent to find her before she finds them.